Short-term cycles of feed deprivation and refeeding promote full compensatory growth in the Amazon fish matrinxa (Brycon amazonicus) - Urbinati, Elisabeth Criscuolo [UNESP]; Jimenez Sarmiento, Sherezada; Takahashi, Leonardo Susumu [UNESP] (Elsevier B.V., 2014)
Developing nutritional strategies that can reduce production costs for the fish industry without affecting productive performance is paramount to make the activity sustainable. We investigated if short-term cycles of feed deprivation and refeeding elicit compensatory growth in matrinxa (Brycon amazonicus) juveniles, using three feeding protocols for 60 days (Phase 1): two levels of deprivation (feed deprivation for two days and refeeding for three - D2R3, or four days - D2R4) and a control level (daily feeding). Following, all fish groups were fed daily at satiation for 15 days (Phase 2). At Phase 1, matrinxa achieved full compensatory growth in both deprivation levels by increasing feed intake and feed efficiency. Overall, deprived fish consumed 40% (D2R3) and 36% (D2R4) less feed than fish fed daily. In Phase 2, growth was similar for all fish. Feed intake increased in both deprived fish, but feed efficiency did not differ among groups and was lower than in Phase 1, indicating a reduced efficiency in feed utilization when food was freely available. We propose that intermittent cycles of feeding represent an effective means to reduce production costs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Feeding protocol; Feed deprivation; Growth performance; Matrinxa; Production costs